Hubungan Pemberian Makanan Pendamping Asi Dini dengan Status Gizi Bayi 0-11 Bulan di Puskesmas Bangko Rokan Hilir - Winda Septiani (STIKes Hang Tuah Pekanbaru, 2014)
The issue in this research is still low percentage breast-fed exclusive and high the percentage of granting dishes - breast milk early in infants 0-11 month in districts chart of the western region of work puskesmas Bangko Rokan Hilir. This research aimed at granting dishes - breast milk early to see relations with nutrition status of baby 0-11 months in districts chart of the western region of work puskesmas Bangko Rokan Hilir. This research is research quantitative with the type of design research cross sectional. Held in districts chart of the western region of work puskesmas bangko rokan hilir from the date 20 may to 20 june 2011, with the number of samples taken with 67 a respondent who uses the technique proportionate random sampling. An interview conducted with a method of collecting data and analysis using a questionnaire used is univariat, bivariat duiji by test chi-square and multivariate tested with the regression safinat logistic uppercut. This research result got that the prevalence of malnutrition by 31,1 %.The average age of granting dishes - breast milk early & < six months of 59,7 %.Analysis of the results obtained the multivariate meaningfui relations between the provision of dishes - breast milk early with nutrition status of baby 0-11 months. An infant who is given dishes - breast milk < six months have a chance the baby ' s status is not normal nutrition 16,694 times compared with an infant who is given dishes - breast milk > six months after controlled by education, knowledge and work